PELATIHAN KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL UNTUK MENINGKATKAN PERILAKU PEDULI PARA PERAWAT - Benita Koesmarsono; Triandini Paramita; Frikson C. Sinambela (Program Studi S1 Psikologi, 2020)
This study aims to improve caring behavior in nurse who worked at Hospital X through spiritual intelligence and emotional intelligence. Spiritual intelligence aspects in this study are critical existential thinking, personal meaning production, transcendental awareness and conscious state expansion. Emotional intelligence aspects in this study are perception of emotion, use of emotion to facilitate thoughts, understanding emotion and manage emotion. The concept that is used in this training is experiencing learning. The material of training were taught and delivered through lecturing, games, discussion, reflection, sharing, audio-visual and writing tasks. Participant in this training are 13 nurses that worked in emergency room, out-patient care and hospitalization care. The design of this study is one-group pretest-posttest design. Nurse’s caring behavior were measured with Caring Behavior Inventory. The result of this study suggest that there was significant differences before and after the training. It showed that spiritual intelligence and emotional intelligence training was effective to improve caring behavior in nurses at Hospital X.